PERFORMANCE AND PERFORMANCE SPACES IN BUKUSU WORK AND CELEBRATORY SONGS - George Wanjala, Kasili (IJRDO - Journal of Social Science and Humanities Research, 2016)
This paper is an examination of the dramatic aspects and the spaces utilized in the delivery of Bukusu work and celebratory songs. By work songs we refer to songs for tapping of white ants while celebratory songs refer to those for twin dances and initiation. The paper opines that apart from the oral delivery of the songs, the drama witnessed and other theatrical aspects are the means through which the songs receive full realization; there are dramatic aspects that make the oral performances complete. The paper therefore investigates the drama that accompanies the oral performances and how it gives live to the songs. Abstinence from conjugal responsibilities during initiation, centrality of the (Bakoki) age grade fold, the ululation performed by the mother(s), the ‘Namachengeche’ concept, the sitting arrangement by the female folk on the day of initiation, sharing of white ants after tapping, the nature and context of the twin dance and other performative spaces constitute the essential components that give life to the oral texts.